Does oxidative stress shorten telomeres?. (3rd May 2017) - Boonekamp, Jelle J.; Bauch, Christina; Mulder, Ellis; Verhulst, Simon
Abstract : Oxidative stress shortens telomeres in cell culture, but whether oxidative stress explains variation in telomere shortening in vivo at physiological oxidative stress levels is not well known. We therefore tested for correlations between six oxidative stress markers and telomere attrition in nestling birds (jackdaws Corvus monedula ) that show a high rate of telomere attrition in early life. Telomere attrition was measured between ages 5 and 30 days, and was highly variable (average telomere loss: 323 bp, CV = 45%). Oxidative stress markers were measured in blood at age 20 days and included markers of oxidative damage (TBARS, dROMs and GSSG) and markers of antioxidant protection (GSH, redox state, uric acid). Variation in telomere attrition was not significantly related to these oxidative stress markers (| r | ≤ 0.08, n = 87). This finding raises the question whether oxidative stress accelerates telomere attrition in vivo . The accumulation of telomere attrition over time depends both on the number of cell divisions and on the number of base pairs lost per DNA replication and, based on our findings, we suggest that in a growing animal cell proliferation, dynamics may be more important for explaining variation in telomere attrition than oxidative stress.